Survey of Seed-Borne Fungi in the Libyan Jamahiriya - ABUGHNIA, ABDULNABI; FARAJ, ISSA S. (The Libyan Journal of Agriculture, 2023)
Seeds of nine crops were tested by routine seed health testing. A total of 21 fungal species representing ten genera were identified and are considered a new record for the Libyan Jamahiriya.